PERAKITAN TEKNOLOGI PENGELOLAAN HARA SPESIFIK LOKASI PADI SISTEM GOGO RANCAH DI DESA SEMAWUNG KECAMATAN ANDONG KABUPATEN BOYOLALI - - Andrias; - Suprihati; Diah Setyorini (Agric, 2016)
ABSTRACTRainfed ricefield, planted at least for one cropping season in a year, depends heavily on rainfall for its water supply. This land generally is low in fertility as indicated by the limited availability of essential plant nutrients in particular nitrogen (N), phosphorus (P), and potassium (K) as well as organic matter. Its productivity is relatively low with a rather erratic precipitation distribution. In order to overcome fertility issue in rainfed land, it is necessary to conduct an integrated nutrient management; one of which is by implementing location specific nutrient management. This study aims to seek the appropriate nutrient management in rainfed paddy field of Semawung village in the sub-district of Andong of Boyolali regency to be provisioned as a technological tool of location specific nutrient management. Research on nutrient management of gogo rancah system-based paddy production was carried out from October 2014 to January 2015. The field experiment was arranged in a Randomized Block Design involving eight treatments and three replications for each treatment. Treatments were combinations of NPK fertilizer, Organofosfat, and straw-based organic fertilizer. Nutrient management using NPK fertilizer and its combination with Organofosfat or organic fertilizer had very significant effect on plant height and number of stem per hill, significantly affected number of panicle per hill, panicle length, and number of fully-filled grain but did not result in difference of fully filled grain percentage and weight of 1000 grains. There was no significant difference between the treatment of 100% of NPK fertilizer and the combination of 75% of NPK fertilizer with straw-based fertilizer regarding these variables: number of stem per hill, number of panicle per hill, panicle length, number of grain per hill, number and percentage of fully-filled grain, weight of 1000 grains, and weight of fresh grain and milled grain yield. Therefore, the latter treatment is feasible as an option of location-specific nutrient management Semawung village.